Differences in the Development and Investment in Human Capital in the Member States of the European Union - Przygodzki, Zbigniew (Comparative Economic Research. Central and Eastern Europe, 2012)
Human capital and knowledge are most important factors of current development processes, contributing to the innovativeness and competitiveness of the economies. The important role of these factors was underlined also in Europe 2020 Strategy. However, due to immaterial character of investment in human capital and because of the high level of decentralization of human capital development policy, these actions are characterized by a relatively low efficiency. Thus, the aim of this paper is firstly to identify the importance of human capital development policy within EU policies. Secondly, it is to identify and conduct a comparative analysis of national differences in human capital development and to identify points of reference for key measures of the development in question. Thirdly, this paper is to specify models of human capital development policy from the perspective of how much involved local authorities are in its implementation and efficiency.